Avaliação ambiental e de influência de variáveis econômicas na cadeia produtiva de proteína suína com a inclusão de biodigestores - Mierlo, Karen Godoi Van (2022)
Human beings have increasingly impacted the environment due to population growth and consumerism. A technological option for minimizing potential environmental impacts and optimizing economic indicators is implementing and using biodigesters in the pork protein production chain: a sector that has also grown in recent years. The biodigestion process generates biogas - which can be used to produce energy, CO2, and biofertilizer - from organic waste as a form of waste treatment. So, the objective of this research was to identify the potential environmental impacts and the influence of economic variables associated with the implantation and use of biodigester in the industrial production of pork protein. For this, a Life Cycle Assessment (LCA) cradleto-gate of the pork production chain was carried out from the production of feed to the exit of the pork protein from the slaughterhouse, ready to be packaged. The LCA results of the composting scenario, which was the waste treatment used, were compared with the new waste treatment's anaerobic digestion scenario. A sensitivity analysis was performed to identify the influence of economic variables based on the Net Present Value (NPV), this financial indicator that brings the amounts invested to the current date. The study showed that the biodigester cost of maintenance and annual operation was the variable that most influenced the NPV, as well as the electricity avoided cost in the slaughterhouse - since the electricity from biodigester was being used, not only the electricity from the grid. Related to the environmental assessment of the pork protein life cycle studied, there was a decrease in the potential environmental impacts generated with the implementation of biodigester waste treatment in the categories of GWP - Global Warming Potential by -1.19% ( for biogenic GWP, there was a decrease of -1.45%, fossil GWP a reduction of -1.21% and for GWP land use and soil transformation the decline was -0.65%). In the resource depletion categories, there was also a decrease in potential impacts (elements was -0.10%, fossil fuels -1.21%, and water scarcity -3.53%). In the potential impact of eutrophication and acidification the composting waste treatment showed less potential for environmental impacts. Thus, this study highlighted the key points, benefits, and limitations of this technology in new projects in the sector.In this way, this study was fundamental to list the key points, benefits, and limitations of this technology in new projects in the sector.